2014
DOI: 10.1136/gutjnl-2013-306502
|View full text |Cite
|
Sign up to set email alerts
|

Non-selective β-blockers are associated with improved survival in patients with ascites listed for liver transplantation

Abstract: NSBB in patients with ascites and refractory ascites listed for liver transplantation are not detrimental, and instead are associated with reduced waitlist death. Our findings argue that NSBB are safe and may confer benefit in patients with ascites complicating end-stage liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
1
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(131 citation statements)
references
References 34 publications
2
123
1
5
Order By: Relevance
“…This is particularly unjustifiable in light of 2 more recent larger studies that have shown a greater survival with NSBB or no differences in survival, respectively. In the first of these studies, a propensity score-matched study in a cohort of patients with cirrhosis on the transplant wait list showed a survival advantage of patients with refractory ascites on NSBB compared to those not on NSBB and, interestingly, showed that the use of carvedilol (a NSBB with vasodilatory properties that has been shown to lead to a larger decrease in blood pressure compared to propranolol [16] ) had an intermediate survival between patients with propranolol (lowest mortality) and those not on NSBB (highest mortality) [17] . The second study, a post-hoc analysis of data from 3 RCTs about V 2 receptor antagonists in the treatment of ascites, showed no differences in mortality between those on and off NSBB, even when adjusted by MELD, mean arterial pressure, dose of beta-blockers or study group (satavaptan vs. placebo) [18] .…”
Section: Ascitesmentioning
confidence: 99%
“…This is particularly unjustifiable in light of 2 more recent larger studies that have shown a greater survival with NSBB or no differences in survival, respectively. In the first of these studies, a propensity score-matched study in a cohort of patients with cirrhosis on the transplant wait list showed a survival advantage of patients with refractory ascites on NSBB compared to those not on NSBB and, interestingly, showed that the use of carvedilol (a NSBB with vasodilatory properties that has been shown to lead to a larger decrease in blood pressure compared to propranolol [16] ) had an intermediate survival between patients with propranolol (lowest mortality) and those not on NSBB (highest mortality) [17] . The second study, a post-hoc analysis of data from 3 RCTs about V 2 receptor antagonists in the treatment of ascites, showed no differences in mortality between those on and off NSBB, even when adjusted by MELD, mean arterial pressure, dose of beta-blockers or study group (satavaptan vs. placebo) [18] .…”
Section: Ascitesmentioning
confidence: 99%
“…The authors showed that after SBP patients on NSBBs had lower blood pressure and a higher risk of hepatorenal syndrome, though it is unclear from the report whether the patients were maintained on NSBBs or not after the SBP. A very recent study assessing 322 patients with ascites (117 refractory ascites) on the waiting list for liver transplant seems to contradict these findings [22]. Indeed, patients on NSBBs had a better survival than patients not taking β-blockers, and this effect was more marked in the group of patients with refractory ascites.…”
Section: Clinical Scenarios For the Treatment Of Portal Hypertensionmentioning
confidence: 63%
“…Because the debate about the use of NSBB in patients with ascites is still on-going, such data might be of major interest. Recent data showed a benefit of NSBB for patients on the transplant waiting list and for patients with ACLF [5], [6]. Propranolol effects may also be due to properties other than reducing portal pressure.…”
Section: Hvpg Hepatic Venous Pressure Gradient Nsbb Non-selective Betmentioning
confidence: 99%